Cross‐polarization reflectance imaging of root caries and dental calculus on extracted teeth at wavelengths from 400 to 2350 nm. Issue 11 (13th July 2018) - Yang, Vincent B.; Curtis, Donald A.; Fried, Daniel
Abstract : The identification of root caries and calculus on tooth roots is of increasing importance with our aging population. Exposed root surfaces are often impacted by erosion, abrasion, calculus and staining which can make the identification and management of caries challenging. Identification of dental calculus on root surfaces and verification of its removal is also important for patient education and to decrease susceptibility to caries and periodontal disease. The objective of this study was to determine how the contrast of root caries lesions and dental calculus varies with wavelength in the visible to near‐infrared. The contrast of suspected root caries lesions and dental calculus on 30 extracted teeth was measured using cross‐polarization reflectance measurements at wavelengths from 400 to 2350 nm. Significantly higher ( P < 0.05) lesion contrast was measured at wavelengths greater than 1460 nm. Stains interfered significantly at wavelengths less than 850 nm yielding non‐diagnostic contrast for root caries lesions. We postulate that the high absorption of water at longer wavelengths reduced the light scattering from the surrounding and underlying normal dentin, thus increasing the lesion contrast. This study indicates that wavelengths beyond 1400 nm are advantageous for imaging calculus and caries lesions on root surfaces due to the high contrast and lack of interference from stain. Abstract : The objective of this study was to determine how the contrast of root caries lesions and dental calculus varies at wavelengths from 400 to 2350 nm. Significantly higher ( P < 0.05) lesion contrast was measured at wavelengths greater than 1460 nm. Stains interfered significantly at wavelengths less than 850 nm yielding non‐diagnostic contrast for root caries lesions. This study indicates that wavelengths beyond 1400 nm are advantageous for imaging calculus and caries lesions on root surfaces.